2004
DOI: 10.1002/ppul.20130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antihypoxemic maneuvers before tracheal aspiration in mechanically ventilated newborns

Abstract: Periodical tracheal aspiration in mechanically ventilated patients is necessary to remove mucus from the airways. In children and adults, this procedure causes transient hypoxemia, which may be prevented by hyperoxia and/or hyperventilation. These findings, however, have not been sufficiently assessed in newborn infants. Thus we investigated the usefulness of hyperoxia and/or hyperventilation as antihypoxemic maneuvers before tracheal aspiration in newborn infants. Our design was a prospective, randomized, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…37 weeks in 11/15, age range: 1-24 days), three techniques to prevent hypoxemia (hyperoxygenation with 10% above baseline, hyperventilation with 50% increase in rate of inflations, and both) were compared with no maneuver. 36 All three techniques resulted in an initial increase in SpO 2 , which remained above baseline during suctioning only with hyperoxygenation alone. Similarly, this was the only technique in which SpO 2 was significantly higher than the control condition at 0, 1, and 5 minutes postsuctioning.…”
Section: Preoxygenation Before Suctioningmentioning
confidence: 87%
“…37 weeks in 11/15, age range: 1-24 days), three techniques to prevent hypoxemia (hyperoxygenation with 10% above baseline, hyperventilation with 50% increase in rate of inflations, and both) were compared with no maneuver. 36 All three techniques resulted in an initial increase in SpO 2 , which remained above baseline during suctioning only with hyperoxygenation alone. Similarly, this was the only technique in which SpO 2 was significantly higher than the control condition at 0, 1, and 5 minutes postsuctioning.…”
Section: Preoxygenation Before Suctioningmentioning
confidence: 87%
“…In NBs, hyperoxia (a 10% increase over baseline fraction of inspired oxygen) led to favorable effects on the reduction of transient hypoxemia resulting from endotracheal aspiration by an open system. (38) Manual restraint maneuvers, through the placement of the hands on the head and feet of NBs in flexed posture, reduced pain scores during the procedure in preterm NBs. (37) The criteria in table 2 are suggested to enhance the safety of the procedure, and they indicate that airway aspiration of intubated NBs, infants, and children be performed for a maximum of 10 seconds (to prevent ventilatory and hemodynamic alterations inherent to disconnecting the patient from the MPV apparatus) and that the vacuum suction pressure should not exceed 360 mmHg.…”
Section: Rationalementioning
confidence: 96%
“…(37) Multisensory stimulation does not alter pain scores after endotracheal aspiration in NBs (C). (38) Rationale When the sedation score was evaluated during endotracheal aspiration in children under MPV, it was found that this procedure does not alter the level of sedation previously used. (32) In NBs under MPV, the use of sedation prior to the procedure did not influence pain scores as measured using the Bernese Pain Scale for Neonates (BPSN), Premature Infant Pain Profile (PIPP), and Visual Analogue Scale (VAS).…”
Section: What Are the Effects Of Analgesia And Sedation On Stress Reamentioning
confidence: 99%
See 1 more Smart Citation
“…No estudo apresentado, procuramos descrever detalhadamente toda a seqüência de procedimentos a serem realizados antes, durante e após a aspiração, como: posicionamento do RN em decúbito dorsal com a cabeça na linha média, pré-oxigenação com 10% de FiO 2 acima da basal, seleção apropriada da sonda de aspiração de acordo com o número de cânula endotraqueal e valor de pressão negativa de 15 a 20 cmHg além da duração do procedimento, que foi de 15 segundos (Hodge, 1991;Skov et al, 1992;Wringtson et al,1999;O'Neal et al, 2001;Day et al, 2002;Akgul e Akyolcu, 2002;Morrow et al, 2004;González-Cabello et al, 2005;Morrow e Argent, 2008 (Maggiore et al, 2003). Carlon et al (1987) (Maggiore et al, 2003).…”
Section: Analise Da Pressão Arterialunclassified